KEEFEKTIFAN MODEL TGT NHT BERBASIS TEORI VAN HIELE TERHADAP HASIL BELAJAR MATEMATIKA (Joyful Learning Journal, 2017)
This research aimed to identify the effectiveness of TGT based on Van Hiele theory compared to the NHT based on Van Hiele theory and STAD model as a controled class towards 5th grade students’ on mathematics learning result of Melati Elementary Schools, Kudus City. It was a Quasi Exsperimental research with Nonequivalent Control Group Design. The populations were all 5th grade students of Melati Elementary School, Kudus City. The sampling technique used was cluster random sampling. The samples were students of 5th class Karangmalang 1 Elementary School (1st experimental class), students of 5th class Karangmalang 3 Elementary School (2nd experimental class), and students of 5th class Karangmalang 2 Elementary School (control class). The result showed that TGT theory model based on Van Hiele was more effective than model of NHT based on Van Hiele theory and STAD model. The result revealed that the mean value of posttest in the 1st experimental class (85,25) was better than the 2nd experimental class (83,11) and control class (79,03). The result showed that the mean value of N-Gain 1st experimental class (0,80) was better than the 2nd experimental class (0,76) and control class (0,71). Penelitian ini bertujuan untuk mengetahui keefektifan model TGT berbasis teori Van Hiele dibandindgkan dengan model NHT berbasis teori Van Hiele dan STAD sebagai kelas kontrol terhadap hasil belajar Matematika siswa kelas V SDN Gugus Melati Kudus. Jenis penelitian yang digunakan adalah Quasi-Experimental dengan bentuk Nonequivalent Control Group Design. Populasi penelitian adalah siswa kelas V SDN Gugus Melati Kecamatan Gebog Kabupaten Kudus. Teknik pengambilan sampel menggunakan cluster random sampling. Sampel yang digunakan siswa kelas V SDN 1 Karangmalang (kelas eksperimen 1), siswa kelas V SDN 3 Karangmalang (kelas eksperimen 2), dan siswa kelas V SDN 2 Karangmalang (kelas kontrol). Hasil penelitian menunjukkan model TGT berbasis teori Van Hiele lebih efektif dari model NHT berbasis teori Van Hiele dan model STAD. Rata-rata hasil postest kelas eksperimen 1 sebesar 85,25, kelas eksperimen 2 sebesar 83,11 sedangkan pada kelas kontrol sebesar 79,07. Rata-rata N-Gain pada kelas eksperimen 1 sebesar 0,80, pada kelas eksperimen 2 sebesar 0,76, sedangkan pada kelas kontrol sebesar 0,71 sehingga peningkatan hasil belajar kelas eksperimen 1 dikategorikan tinggi, kelas eksperimen 2 dikategorikan tinggi, dan pada kelas kontrol dikategorikan tinggi.